(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
This Study was carried out at the Center of Animal production ( Fedio), Faculty of Agriculture, in order to evaluate the effect of repetition collection on some semen characteristics of Brown, Black and White types of local roster in syria, Where semen was collected daily, twice and three times a week. The results showed no difference(p<0.05) in semen color that was pearly white in both studied types, while there were significant differences in all other studied indicators; volume, total movement, concentration and Low dead sperb ratio. The results also showed a significant increase in the average volume ejaculate in the brown type compared to black and white type when semen were collected twice a week, where it was about 0.7 and 0.5 ml respectively. Indeed, concerning the average of the total movement, there were no significant differences (p>0.05) between the number of times of collection in the Brown type and Black and White type. The average value of total movement in the Brown type was 93.31, 95.1, and 93.22% using daily collection, twice a week and three times a week respectively whereas it was 88.12, 90.02 and 87.14% respectively in White and black type. Additionally, the average concentration was 5.82, 5.91 and 5.93 million sperm/ ml respectively in the Brown type, and 3.21, 3.33 and 3.34 million sperm/ml respectively in white and black. Finally, our results showed that There were no significant differences between the mean percentage of dead sperm between the both studied types; that attained 6.69 , 4.88 and 6.78% respectively in the Brown and 11.88, 9.98, and 12.86% respectively in the Black and White. أجري هذا البحث في مركز بحوث الإنتاج الحيواني بفيديو، التابع لكلية الزراعة في جامعة تشرين ومخابر الكلية بهدف دراسة تأثير تكرار جمع السائل المنوي على بعض خصائصه عند نمطين من الديك المحلي في سوريا (بني اللون، أبيض وأسود اللون)، حيث تم جمع السائل المنوي يومياً، مرتين أسبوعياً، وثلاث مرات أسبوعياً. أظهرت النتائج تماثل لون السائل المنوي فهو أبيض لؤلؤي عند النمطين المدروسين، في حين تبين وجود فروق معنوية 0.05) >P ) بين النمطين الظاهرين المدروسين للريش في جميع المؤشرات المدروسة الأخرى (الحجم، الحركة الإجمالية، التركيز، انخفاض نسبة الحيوانات المنوية الميتة). كما أظهرت النتائج تفوق معنوي عند جمع السائل المنوي مرتين بالأسبوع للنمط بني اللون على النمط أبيض وأسود اللون من حيث متوسط حجم القذفة، إذ بلغ حوالي 0.7 و 0.5 مل على التوالي بالمقارنة مع الجمع يومياً والذي بلغ حوالي 0.3 و 0.1 مل على التوالي والجمع ثلاث مرات بالأسبوع حيث بلغ حوالي 0.33 و 0.12 مل على التوالي، في حين لا يوجد أي فروق معنوية(0.05<p) بين عدد مرات الجمع عند النمط بني اللون والنمط أبيض وأسود اللون، وذلك من حيث متوسط الحركة الإجمالية إذ بلغت قيمة هذا المتوسط عند الجمع يومياً ومرتين بالأسبوع وثلاث مرات بالأسبوع للنمط بني اللون 93.31 و 95.12 ، و 93.22 % على التوالي، و عند النمط أبيض وأسود اللون القيم 88.12 و 90.02 و 87.14 % على التوالي، و كذلك من حيث متوسط تركيز الحيوانات المنوية، إذ بلغت قيمة هذا المتوسط عند النمط بني اللون عند فترات الجمع السابقة 5.82 و 5.91 و 5.93 مليار نطفة/مل على التوالي، والنمط أبيض وأسود اللون 3.21 و3.33 و3.34 مليار نطفة/ مل على التوالي، كما تبين أيضاً عدم وجود فروق معنوية بين متوسط نسبة الحيوانات المنوية الميتة عند فترات الجمع السابقة بين النمط بني اللون إذ بلغ 6.69 و 4.88 و % 6.78 على التوالي ، والنمط أبيض وأسود اللون 11.88 و 9.98 و 12.86 % على التوالي .